Assisted reproductive technologies for endangered species conservation: developing sophisticated protocols with limited access to animals with unique reproductive mechanisms. Issue 5 (16th February 2019) - Herrick, Jason R
Abstract: Assisted reproductive technologies (ARTs) have been proposed as a means of overcoming the significant challenges of managing small, isolated populations of endangered species in zoos. However, efficient protocols for ARTs do not exist for most endangered species. This review will focus on research efforts to characterize unique reproductive mechanisms and develop species-specific ARTs. Central to these studies are assays to measure steroid metabolites in urine or feces and/or training programs to allow unrestrained blood collections and ultrasound evaluations. The resulting information about estrous cycle dynamics, combined with studies of semen collection and processing, provides the foundation for the development of artificial insemination (AI). In vitro fertilization and embryo transfer are also discussed in relation to the advantages these techniques could provide relative to AI, as well as the significant challenges involved with technologies that require oocytes and embryos. Finally, an argument is made for additional research of nontraditional model species (e.g., domestic cats and dogs) and the development of novel models representing unique taxa. Whether these species are studied by zoo-based researchers with the expressed intent of developing ARTs for conservation or academic scientists interested in basic biology, the resulting information will provide a unique, evolutionary perspective on reproduction that could have wide-reaching benefits. The more information we have available, the better our chances will be of developing effective ARTs and making a difference in conservation efforts for endangered species. Abstract : Reproductive biologists developing ARTs for wildlife face the challenge of developing sophisticated protocols requiring significant amounts of information for species that have never been studied before and are not readily available to study now.